THE REASONS FOR REVELATION ACCORDING TO THE PERSPECTIVE OF CLASSICAL AND CONTEMPORARY MUSLIM SCHOLARS - Nadia, Husna (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2025)
There are many scholars who have differing opinions in defining the reasons for revelation, including Az-Zarqani, Ash-Shabuni, Shubhi Shaleh, and Manna’ Khalil Al-Qattan, among others. However, although the wording of these definitions varies slightly, they all conclude that Asbab an-Nuzul refers to the events or incidents that serve as the background for the revelation of Quranic verses, aimed at responding to, explaining, and resolving issues arising from those events. The reasons for revelation serve as a historical source that provides explanations for the revelation of Quranic verses and offers contextual understanding of its commandments. This article aims to explore the definition of the reasons for revelation from classical to contemporary muslim scholars, highlighting its significance and the importance of its study. It employs library research to examine various scholarly opinions on the reasons for revelation. This study is highly beneficial in understanding the context of revelation, applying Quranic verses to different cases and situations, and reducing the likelihood of misinterpretation, which increases when the historical background of the reasons for revelation is ignored. In conclusion, although scholars define the reasons for revelation in different ways, they all ultimately agree that it refers to the events or incidents that serve as the background for the revelation of Quranic verses.